Harnessing Nanoemulsion Technology for Enhanced Delivery of Canagliflozin in Type 2 Diabetes Therapy - Lakavath Sunil Kumar, (Asian Journal of Pharmaceutics (AJP), 2025)
Introduction: Canagliflozin, a selective sodium-glucose cotransporter-2 inhibitor indicated for the management of type 2 diabetes mellitus (T2DM), is limited by poor aqueous solubility and suboptimal bioavailability, which impede its therapeutic potential. This study aimed to develop and comprehensively characterize a nanoemulsionbased delivery system to enhance the solubility, stability, and bioavailability of Canagliflozin. Preformulation analyses confirmed the drug’s high solubility in methanol and DMSO, contrasted by poor water solubility and unsatisfactory micromeritic properties, indicating the necessity for formulation intervention. Materials and Methods: Nanoemulsions were prepared using appropriate oil, surfactant, and cosurfactant systems, and subjected to sonication and high-pressure homogenization techniques to optimize droplet size and dispersion uniformity. Results and Discussion: Among the various formulations, F5 emerged as the most promising, exhibiting a droplet size of 68.1 nm and superior homogeneity. Differential scanning calorimetry of F5 revealed a marked reduction in the drug’s melting point, suggesting enhanced dispersion and possible conversion to an amorphous state. Fouriertransform infrared spectroscopy indicated no significant chemical degradation, though minor spectral shifts suggested non-covalent interactions between the drug and excipients. Collectively, the results support the successful development of a stable nanoemulsion formulation capable of enhancing Canagliflozin’s physicochemical and biopharmaceutical properties. Conclusion: This work underscores the potential of nanoemulsion technology as a strategic platform for improving the delivery of poorly soluble antidiabetic agents, thereby contributing to more effective and reliable therapeutic outcomes in the management of T2DM.